The Evolution of Religious Influence on Policy: A Review of Historical and Contemporary Studies - Babayo Sule (Religion and Policy Journal)
Research Problem: This review aims to explore the dynamic relationship between religion and policymaking, tracing its historical roots and examining its contemporary manifestations. It seeks to understand how religious beliefs, institutions, and ideologies have influenced public policy throughout history and continue to shape governance and societal norms.